The relationship between intraocular pressure and estimated intracranial pressure in patients with normal tension glaucoma - MS, Syamil; AN, Rona; CH, Jemaima (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aims to determine the relationship between intracranial pressure (ICP) and intraocular pressure (IOP) in patients with normal-tension glaucoma (NTG) who were already on anti-glaucoma treatment using an estimated ICP (estICP) and translaminar pressure difference (estTPD) formula. A cross-sectional comparative study consisted of 66 subjects (66 eyes) who were divided into NTG (n=33) and normal (n=33) group was conducted from 1st November 2017 until 31st May 2020 at a tertiary hospital in Malaysia. After obtaining consent from subjects, ocular and systemic data including IOP, visual field testing, axial length, central corneal thickness (CCT), peripapillary and macular retinal nerve fibre layer evaluation as well as blood pressure (BP) and body mass index (BMI) were collected. The estICP (mm Hg) was calculated as 0.44 x BMI (kg/m2) + 0.16 x diastolic blood pressure (mmHg) – 0.18 x age (years) – 1.91. The estTPD was derived from this calculated value, where estTPD (mm Hg) = IOP – estICP. Analysis showed there was no significant difference in estimated ICP between NTG and normal subjects [mean difference (95% CI): 0.37 (-1.39, 2.12), p=0.679]. The difference in estTPD between NTG and normal subjects were found to be statistically insignificant too [mean difference (95% CI): -1.24 (-2.95, 0.47), p=0.149]. The variables significant in multivariate model included best corrected visual acuity (p=0.028), retinal nerve fiber layer (RNFL) (p=0.003), average macular (p=0.002) and estTPD (p=0.008). The EstTPD was found to be protective towards NTG, which the unit increased in estTPD will decreased the odds of having NTG by 26.5% [Adj. OR (95% CI): 0.735 (0.586, 0.922), p=0.008]. In conclusion, ICP was correlated in increased in IOP. A higher TPD may be associated with a lower chance of developing NTG.